Minimally Invasive Correction of Proximal Phalanx Malunion Using Cannulated Headless Screws: A Case Series - Sibarani, Jonathan Junius; Satria, Oryza; Aprilya, Dina (CoinReads Media Prima, 2025)
Introduction: Malunion of the proximal phalanx can result in significant aesthetic and functional impairments, including malrotation, finger scissoring, and diminished grip strength. Conventional treatment involves open osteotomy with plate and screw fixation, which is associated with drawbacks such as surgical site scarring, prolonged rehabilitation, and tendon or soft tissue adhesions. This case series evaluates a minimally invasive technique using cannulated headless screws as an alternative approach for correcting proximal phalanx malunion. Methods: Three patients with proximal phalanx malunion underwent a minimally invasive procedure. The technique involved two small incisions: one for osteotomy and another for guide wire insertion, followed by fixation with a cannulated headless screw under fluoroscopic guidance. Postoperative outcomes were assessed at three months, focusing on hand function, deformity correction, and complications. Results: At the three-month follow-up, all patients demonstrated significant improvements in hand function, with restored alignment and no reported malrotation or scissoring. Grip strength was enhanced, and no complications, such as infection or hardware failure, were observed. Patients reported minimal scarring and faster recovery compared to traditional open approaches. Conclusion: The minimally invasive approach using cannulated headless screws offers a promising alternative for correcting proximal phalanx malunion. It minimizes soft tissue trauma, reduces scarring, and promotes faster rehabilitation while achieving favorable functional outcomes. Further studies with larger cohorts are warranted to validate the efficacy and long-term outcomes of this technique.